Eksistensi Ibu Rumah Tangga dalam Peningkatan Ekonomi Keluarga (Studi Kasus: Jorong Aie Angek Kenagarian Koto Tinggi) - Rahwindi Angelia Putri; Dewi Manda Angraini (Lembaga Yasin AlSys, 2025)
The limited number of studies on the active role of housewives in improving family economies forms the background of this research, despite the significant impact of this phenomenon on household economic well-being. This study aims to describe the contributions of housewives and the various activities they undertake to enhance family income in Jorong Aie Angek, Kenagarian Koto Tinggi. A qualitative method was employed, using purposive sampling to select 20 informants. Data were collected through in-depth interviews and analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that housewives play a strategic role in increasing household income. In addition to fulfilling domestic responsibilities, they engage in supplementary work such as running small shops, working as daily laborers, selling fried snacks, and sewing. The primary motivation for housewives to seek income-generating activities stems from economic pressures, particularly inadequate earnings from their husbands. The income generated by housewives significantly contributes to meeting household needs and enhancing family welfare. The main conclusion of this study is that the role of housewives is crucial in supporting family economic resilience. The implications highlight the need for policy-makers and communities to support the economic empowerment of housewives, and open opportunities for further research on success factors in women's household-level economic activities.